2018
DOI: 10.1186/s12245-018-0206-7
|View full text |Cite
|
Sign up to set email alerts
|

Deciding to lead: a qualitative study of women leaders in emergency medicine

Abstract: BackgroundThe aim of this study is to highlight career paths of senior women leaders in academic emergency medicine (EM) to encourage younger women to pursue leadership.MethodsThis was a qualitative study using semi-structured interviews with female EM leaders. We interviewed 22 recognized female leaders selected using criterion-based sampling and a standardized script of open-ended questions derived from the Intelligent Career Model. Questions were related to job purpose, skills, and networking. Interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Kang and Kaplan explain that just as many women are in the pipeline as men, but they are excluded at each stage of their professional lives, from recruitment and recommendation to evaluation, promotion, training, and compensation [30]. Women also report being disrespected by colleagues, being held to a higher standard than male colleagues, being treated less formally than male colleagues (being introduced by their first name instead of by their formal titles), and not being invited for major talks like grand rounds [31].…”
Section: Leaders In Em Need To Develop Recruitment and Retention Strategies That Focus On Gender Equity Ensuring Women Are Represented Onmentioning
confidence: 99%
“…Kang and Kaplan explain that just as many women are in the pipeline as men, but they are excluded at each stage of their professional lives, from recruitment and recommendation to evaluation, promotion, training, and compensation [30]. Women also report being disrespected by colleagues, being held to a higher standard than male colleagues, being treated less formally than male colleagues (being introduced by their first name instead of by their formal titles), and not being invited for major talks like grand rounds [31].…”
Section: Leaders In Em Need To Develop Recruitment and Retention Strategies That Focus On Gender Equity Ensuring Women Are Represented Onmentioning
confidence: 99%
“…A qualitative rapid research design was deemed appropriate to explore how the leaders of small entrepreneurial businesses were navigating the business challenges of the COVID-19 crisis in real-time (Kuckertz et al, 2020). Previous research has shown qualitative research is not only useful in the rapid response research context (Finlay et al, 2013), but appropriate for the study of crisis leadership (Guptill et al, 2018;E.H. James & Wooten, 2010;Moore, 2018) and in areas where existing knowledge is limited (Miller, 1992).…”
Section: Qualitative Rapid Response Researchmentioning
confidence: 99%
“…Most studies focused on academic medicine, with studies exploring aspirations of medical students, 29 practicing faculty, 28,[30][31][32][33][34] and successful senior leaders. [35][36][37][38][39] Four studies focused on women physicians in rural practice, [40][41][42][43] and two studies explored women physicians' professional experience coming from Native American 20 and Latina 44 backgrounds. Three studies explored physician burnout.…”
Section: Gendered Language and Behavior Inform Howmentioning
confidence: 99%